2021
DOI: 10.1002/solr.202000672
|View full text |Cite
|
Sign up to set email alerts
|

Strain Engineering of Metal–Halide Perovskites toward Efficient Photovoltaics: Advances and Perspectives

Abstract: Due to the impressive optoelectronic properties, metal–halide perovskites (MHPs) have drawn much attention in the field of next‐generation photovoltaics, and perovskite solar cells (PSCs) based on MHPs as light absorbers have reached a certified power conversion efficiency (PCE) of 25.5% in 2020. Despite the great progress, it is still challenging to fabricate high‐quality MHP films. Due to the “soft” ionic nature of MHPs, their polycrystalline films suffer from inevitable residual strain, which is found to no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 71 publications
(80 reference statements)
0
34
0
Order By: Relevance
“…Also, the uncontrollable crystallization of perovskite crystal will induce residual strains in the resultant perovskite film to have negative impact on the optoelectronic properties and stability of the film. [29,30] As expected, deeper understanding on the crystallization dynamics of solution-processing perovskite film and characteristics of Sn-based perovskites are of great significance toward achieving efficient Sn-based PSCs. So far, there are many comprehensive reviews in this field focusing on the current development and future perspective of Sn-based perovskite in terms of preparation, stability, and efficiency of their PSCs.…”
Section: Introductionmentioning
confidence: 86%
“…Also, the uncontrollable crystallization of perovskite crystal will induce residual strains in the resultant perovskite film to have negative impact on the optoelectronic properties and stability of the film. [29,30] As expected, deeper understanding on the crystallization dynamics of solution-processing perovskite film and characteristics of Sn-based perovskites are of great significance toward achieving efficient Sn-based PSCs. So far, there are many comprehensive reviews in this field focusing on the current development and future perspective of Sn-based perovskite in terms of preparation, stability, and efficiency of their PSCs.…”
Section: Introductionmentioning
confidence: 86%
“…On the other hand, strain issue remains as another challenge for inorganic PeSCs, which includes intrinsic lattice strain and extrinsically induced strain. [26] Particularly, the latter is mainly induced by thermal expansion mismatch between the perovskite film with high thermal expansion coefficient (α TE : ≈10 −4 K −1 ) and the underlayer with much lower α TE , such as above-mentioned TiO 2 , SnO 2 , or NiO x with α TE of 0.1 ∼ 2 × 10 −5 K −1 . [27][28][29] In addition, the large temperature gradient (△T) from perovskite formation temperature (i.e., >160 °C for CsPbI 2 Br) to room temperature aggravates such mismatch.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that stress accumulation could induce lattice distortion, reduce the bond strength between atoms and the formation energy of defects. [ 51 ] As a result, it led to more point defects and dislocations, which was not conducive to the migration of free charge carriers. [ 51 ] In addition, stress might promote the phase separation of the mixed halides perovskite.…”
Section: Resultsmentioning
confidence: 99%
“…[51] As a result, it led to more point defects and dislocations, which was not conducive to the migration of free charge carriers. [51] In addition, stress might promote the phase separation of the mixed halides perovskite. [4,52] These adverse impacts will in turn contribute to the accumulation of strain, forming a vicious circle.…”
Section: Characterizations For Thmaac and Btcic-4cl In Cspbi 2 Br Per...mentioning
confidence: 99%
See 1 more Smart Citation